2014
DOI: 10.1681/asn.2013080836
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Renal Toxicity in Mice Administered the Marine Biotoxin Domoic Acid

Abstract: Domoic acid (DA), an excitatory amino acid produced by diatoms belonging to the genus Pseudo-nitzschia, is a glutamate analog responsible for the neurologic condition referred to as amnesic shellfish poisoning. To date, the renal effects of DA have been underappreciated, although renal filtration is the primary route of systemic elimination and the kidney expresses ionotropic glutamate receptors. To characterize the renal effects of DA, we administered either a neurotoxic dose of DA or doses below the recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…In humans, a high, single-exposure dose of DA can cause amnesic shellfish poisoning (ASP), which involves symptoms of amnesia, seizures, coma, and in extreme cases, death. Even chronic, low-level consumption of DA may lead to kidney damage, cognitive deficit, and impairment of fetal development, making DA outbreaks an important human health problem (710). Similar neurotoxic symptoms have been observed in birds and marine mammals such as sea lions, which suffer spatial memory impairment linked to DA consumption, likely leading to increases in sea lion strandings (11).…”
mentioning
confidence: 99%
“…In humans, a high, single-exposure dose of DA can cause amnesic shellfish poisoning (ASP), which involves symptoms of amnesia, seizures, coma, and in extreme cases, death. Even chronic, low-level consumption of DA may lead to kidney damage, cognitive deficit, and impairment of fetal development, making DA outbreaks an important human health problem (710). Similar neurotoxic symptoms have been observed in birds and marine mammals such as sea lions, which suffer spatial memory impairment linked to DA consumption, likely leading to increases in sea lion strandings (11).…”
mentioning
confidence: 99%
“…Elderly consumers had higher susceptibility to DA toxicity in the 1987 Canadian DA poisoning event summarized by Perl et al (1990) and aged rats have shown higher susceptibility to DA toxicity, potentially due to impaired renal function, increased blood-brain barrier permeability, or loss of intrinsic neuroprotective mechanisms during brain aging (Hesp et al 2007; Hesp et al 2004; Kerr et al 2002). Renal filtration is the primary route for DA elimination and impaired renal function can increase DA toxicity in mice and rats (Funk et al 2014; Suzuki and Hierlihy 1993). …”
Section: Discussionmentioning
confidence: 99%
“…The use of this consumption rate (6 clams·day −1 ) and a single body weight (70kg) for exposure calculations risks the omission of temporal, demographic, and spatial variation in toxin exposure found in other recreational fisheries (Burger and Gochfeld 2011; Gochfeld and Burger 2011; Marien 1996). Consumers who eat more than six clams in a meal, weigh less than 70 kg, or are otherwise sensitive to DA toxicity (children, pregnant women, elderly, and those with renal dysfunction) may not be adequately protected by current DA regulations (Doucette et al 2004; Doucette et al 2000; Funk et al 2014; Hesp et al 2007; Maucher and Ramsdell 2007; Perl et al 1990). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides typical food poisoning symptoms, short term memory loss, confusion, and disorientation are observed in ASP. Although higher levels of DA are needed for intoxication, it is a heat stable toxin that can cause kidney damage at levels several orders of magnitude lower than those that cause neurological symptoms [5,6]. It acts by stimulating the glutamate receptors.…”
Section: Introductionmentioning
confidence: 99%